Oxford handbook of psychology in India/ edited by Girishwar Mishra (New Delhi, 2011)
Psychology in India is emerging as a multi-modal, multi-method, and culturally-sensitive human science discipline that bridges the gap between the spirit of science and cultural sensibilities. The Handbook of Psychology in India is a step-by-step guide to the new directions charted by Indian psychology in recent times. It documents the paradigmatic shifts, developments, and transformations in the discipline, and features scholarship that recognizes contributions from indigenous knowledge systems as well as contemporary developments in major subfields. Wide-ranging and comprehensive, it discusses: multiple methods, diverse theoretical perspectives, and culturally informed analyses critical conceptual, empirical, and cultural issues of contemporary significance state-of-the-art accounts of developments in the domains of emotion, cognition, consciousness, prosocial behaviour, group level processes, the self and identity key methodological developments and new directions in psychological research contributions from both researchers and practitioners of psychology This unique volume presents authoritative and exhaustive analyses of substantive processes and phenomena relating to the self, identity, emotion, motivation, group behaviour, justice, organization, environment, values, gender, health, and well-being.
Keywords: "Psychology, Psychology and philosophy, India-Psychology"